Rare red eggs of the Common Guillemot (Uria aalge): birds, biology and people at Bempton, Yorkshire, in the early 1900s. Issue 1 (April 2018) - Birkhead, T. R.; Montgomerie, R.
Abstract : Huge numbers of Common Guillemot ( Uria aalge ) eggs were harvested by local men known as "climmers" (climbers) at Bempton Cliffs, Flamborough, Yorkshire, until 1954 when egg collecting became illegal. Guillemot eggs are more variable in colour and pattern than those of any other bird. Egg collectors (oologists) particularly favoured sets of unusually coloured eggs laid by the same bird. Red guillemots eggs were extremely rare and eagerly sought. An example of one such egg known as the "Bempton Belle" was found in the collection of J. W. Goodall (active between about 1896 and 1909), and was celebrated in a poem. What was probably another red egg, known as the "Metland Egg", was collected each year at Bempton between 1912 and 1938. The current whereabouts of the Metland eggs is unknown. We estimate that females laying red eggs occur less than once in a thousand (or ten thousand). We also speculate about the factors responsible for red eggs and why such eggs are so rare.